Improving Fine Motor Skills Through Sewing Activities In Early Childhood In Kindergarten Almahyra, Hamparan Perak District - Wardah Syahira; Rika Widya (International Journal of Society and Law, 2025)
Fine motor development is a very substantial development for early childhood. Fine motor development also determines a child's ability and success in the academic field and life skills at a later stage. Therefore, there is a need for activities that can support and develop fine motor skills in early childhood. The purpose of this study is to improve fine motor skills through sewing activities in early childhood at Almahyra Kindergarten, Hamparan Perak District. The research method used in this study is Classroom Action Research (PTK). This research has two stages, namely: cycle I and cycle II, each cycle consists of: planning, action, observation and reflection. In this study, each cycle has two meetings, namely the first meeting and the second meeting.